Akibat Hukum terhadap Pembelian Suatu Barang Secara Online - I Gusti Bagus Guna Mahayana; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Problems related to customer affairs will be something that is always in the spotlight for a very long time then the losing party is always on the customer side. The rights that have been promised by business actors who prioritize quality do not match customer expectations. The lack of customers regarding the legal basis and what should be their rights is very weak, this is the opportunity to get more results and do not carry out procedures that should be the obligation of entrepreneurs. So that many violations occur even to the point of violating the law and harming customers. This study aims to examine the legal arrangements regarding the purchase of goods online and examine criminal sanctions against online objects that commit fraud. This study uses a normative method because there are still vague norms, with a legislative and conceptual approach. The data used is from library data collected through literature research and reviewing the legislation. After the data was collected, it was then analyzed by descriptive qualitative data analysis. The results of the study indicate that the legal regulation of an act of business actors to consumers in online buying and selling includes an act that is prohibited for business actors by fulfilling certain elements in accordance with existing regulatory provisions and has been contained in the 2015 Criminal Code Law. in 6 articles, starting from Article 613 to Article 618, then the sanctions applied can be in the form of administrative sanctions or imprisonment